HYPERTROPHIC CARDIOMYOPATHY: GENETIC ALTERATIONS, PATHOGENESIS AND PATHOPHYSIOLOGY - N. T. Vatutin; G. G. Taradin; M. S. Maron (Российский кардиологический журнал, 2014)
The review is dedicated to the description of genetic alterations, pathogenetic mechanisms and pathophysiology of hypertrophic cardiomyopathy, based on the analysis of current up to date information. A contemporary data is provided on the role a plenty discovered mutations of structural, contractile and regulatory sarcomere proteins in cardiomyopathy. The main hypotheses of pathogenetic processes are highlighted, especially the disordered calcium exchange. The importance of genetic testing of patients with hypertrophic cardiomyopathy and their relatives is underlined.The review concerns the basic pathophysiologic characteristics of the disease according to their diagnostic, clinical and prognostic value. Except the description of pathophysiologic properties, as a matter of fact, the obstruction of outflow in the left ventricle, diastolic dysfunction, myocardial ischemia and rhythm disorders, the contemporary instrumental diagnostic methods (positron-emission tomography, computed tomography) in early diagnostic and monitoring of the disease.